Phylogenetic analysis of Dioscorea (Dioscoreaceae) from Japan and adjacent regions based on plastid and nuclear DNA sequences, with special reference to the taxonomic status of selected taxa. (21st October 2021) - Noda, Hiroshi; Fuse, Shizuka; Yamashita, Jun; Poopath, Manop; Pooma, Rachun; Tamura, Minoru N
Abstract: To clarify phylogenetic relationships among Japanese Dioscorea taxa and to re-examine taxonomy based on these relationships, we conducted molecular phylogenetic analyses of four plastid regions [ trnK (including matK ), rbcL, atpB and trnL-F ] and two nuclear regions ( PHYC and 18S rDNA) for all Dioscorea taxa from Japan and selected taxa from adjacent regions. Although species are often sympatric and variation in leaf shape is relatively wide within species and not clearly demarcated between species, our results suggest that Japanese Dioscorea spp. do not hybridize. Our results also resolve several taxonomic issues surrounding Japanese species. We confirm that D. japonica, D. polystachya, D. pseudojaponica and D. tabatae, which are morphologically similar, are distinct species. Further, plants from the Daito Islands identified as D. luzonensis, which have never been observed to flower to our knowledge, are attributable to D. pseudojaponica . Dioscorea zentaroana, often treated as a synonym of D. asclepiadea, was found to be distinct from the latter. Dioscorea izuensis should be treated as D. collettii var. izuensis . In conclusion, 16 species and three varieties of native Dioscorea should be recognized in Japan.